2009
DOI: 10.1017/s1049023x00006555
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Tube and Intubating Laryngeal Mask Insertion in a Manikin by First-Responder Trainees after a Short Video-Clip Demonstration

Abstract: Introduction:This study was performed in the Finnish Defense Forces to assess the potential applicability and value of short video clips as educational material to teach advanced airway management and as the first means of introducing the use of a laryngeal tube (LT) or an intubating laryngeal mask (ILMA) to inexperienced, military, first-responder trainees with no prior hands-on experience.Methods:The 60 non-commissioned medical officers participating in this study were randomly assigned into one of two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…In this study, we hypothesized that LT would provide better outcomes, because several reports have indicated that LT insertion is very easy. 21,22 Therefore, we aimed to determine whether the speedy insertion might shorten the interruption of chest compressions and thereby improve the prognosis of patients with OHCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we hypothesized that LT would provide better outcomes, because several reports have indicated that LT insertion is very easy. 21,22 Therefore, we aimed to determine whether the speedy insertion might shorten the interruption of chest compressions and thereby improve the prognosis of patients with OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Furthermore, LT has been successfully used by paramedics to treat cases of OHCA. [23][24][25] Therefore, although no studies have directly compared LM and LT, it is possible that the time for LT insertion might be shorter than that for LM insertion, which might improve the prognosis and outcomes for patients with OHCA.…”
Section: International Consensus On Cardiopulmonary Resuscitation Andmentioning
confidence: 99%
“…Dies konnten Jokela et al in einer Untersuchung mit unerfahrenen Soldaten zeigen, die sich in der Ausbildung zum First Responder befanden [31]. Beide Hilfsmittel können bei Patienten aller Altersgruppen zur Anwendung kommen, da beide Produkte in einer Vielzahl von Größen erhält-lich sind.…”
Section: Propofolunclassified
“…Bei den notfallmedizinisch noch unerfahrenen Ärzten der Bw kam es sogar zu weniger Schwierigkeiten bei der Einlage des LT (lediglich eine Replatzierung erforderlich) als bei den im Rettungsdienst täti-gen Kollegen (n=4), wenngleich auch keine statistische Signifikanz erreicht wurde. Überraschend war die hohe Rate an Problemen bei der Platzierung des LT in der Gruppe der zivilen NA von 40%, zumal die Anwendung des LT am Modell [15] und am Patienten [18] auch ohne vorheriges aufwendiges Training mit einer hohen Erfolgsquote beschrieben wird. Zwar war der LT in diesem Rettungsdienstbereich neu eingeführt worden, jedoch wurde zuvor eine ausführliche theoretische und praktische Fortbildung durchgeführt.…”
Section: Atemwegssicherung Mithilfe Des Larynxtubusunclassified